Collective identity and resilience in the management of common pool resources. Issue 2 (August 2012) - Mosimane, Alfons W.; Breen, Charles; Nkhata, Bimo A.
Effective management of common pool resources through collective action is dependent upon the efforts of the resources users to establish an identity that is held collectively. It is widely accepted that the term common pool resources implies a resource that is common to a 'pool' of people, the resource users. Their interests in the resource connect users and potential users, and we propose that the more strongly they identify with the resources and commit to act collectively, the stronger the collective action. Achieving sustainable use of common pool resources is thus determined by the interplay between collective identity and collective action. But collective identity as defined by the resource and its users is dynamic, making the identity vulnerable in directing the behaviour of users. In this paper, we draw on collective identity and resilience theories to develop a framework for exploring the role of collective identity in understanding collective action in the management of common pool resources. We suggest that two key attributes of collective identity – identification and affective commitment, provide the premise for interpreting, tracking and directing change in collective identity. We interpret how the interactions between the two attributes contribute to resilience of common pool resources as complex social-ecological systems.